2019
DOI: 10.1016/j.eatbeh.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Parental body dissatisfaction and controlling child feeding practices: A prospective study of Australian parent-child dyads

Abstract: The aim of the present study was to examine whether parents' reported use of controlling feeding practices (restrictive feeding and pressure to eat) change over 6 months, and whether parents' concerns about their own weight and shape are prospectively associated with increasing use of controlling feeding practices. Participants were 48 Australian parents (92% female; M age = 37.8 years) who completed questionnaires twice, with a 6-month time lag, regarding a target child aged 7.6 years on average (52% female).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…This result should be further explored in future studies since, as Doley et al (2020) claimed, there are scarce studies that include males. In this sense, it would also be interesting to consider other variables in the family environment that may explain children's body dissatisfaction, such as critical comments and teasing by parents (Dahill et al, 2021), communication style (Hitti et al, 2020), eating habits (de Oliveira da Silva et al, 2018;Webb and Haycraft, 2019;Burnettea and Mazzeo, 2020), and physical activity (Matthews-Ewald et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result should be further explored in future studies since, as Doley et al (2020) claimed, there are scarce studies that include males. In this sense, it would also be interesting to consider other variables in the family environment that may explain children's body dissatisfaction, such as critical comments and teasing by parents (Dahill et al, 2021), communication style (Hitti et al, 2020), eating habits (de Oliveira da Silva et al, 2018;Webb and Haycraft, 2019;Burnettea and Mazzeo, 2020), and physical activity (Matthews-Ewald et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that, in a sample of children aged 3-7 years, parental dissatisfaction as assessed by a silhouette scale correlated with child dissatisfaction (Kościcka et al, 2016). Similarly, Webb and Haycraft (2019) highlight the link between body dissatisfaction and disadaptative eating habits of parents and the body dissatisfaction of children aged 6-9 years.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…In turn, maternal excess weight significantly increases offspring's obesity risk via epigenetic effects in utero (Saben et al, 2016;Turner & Robker, 2014). In the postpartum period, associations between maternal body image and excess weight gain/retention may contribute to the development of potentially problematic parent-child feeding interactions and practices in early childhood (Haire-Joshu & Tabak, 2016;Hauff & Demerath, 2012;Webb & Haycraft, 2019) that may compromise children's ability to engage with satiety cues (e.g., Birch, Fisher, & Davison, 2003) and thereby promote obesity risk (e.g., Afonso et al, 2016;Graziano, Calkins, & Keane, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The potential negative impact that maternal body dissatisfaction can have on mothers' mental health (i.e., depression) and/or unhealthful eating behaviour (i.e., binge eating) may reduce her engagement in practices, such as breastfeeding, that assist to combat excess body weight (e.g., de Jager, Skouteris, Broadbent, Amir, & Mellor, 2013;Goldschmidt et al, 2014;Hauff & Demerath, 2012;Stice & Shaw, 2002;Torgersen et al, 2010). In turn, associations between maternal body image and factors implicated in health behaviour (i.e., mental health symptoms; disordered eating patterns) may influence the quality of early parent-child interactions, including potentially problematic child feeding practices (e.g., Bergmeier et al, 2016;Farrow & Blissett, 2005;Haire-Joshu & Tabak, 2016;McPhie, Skouteris, Daniels, & Jansen, 2014;Stang & Loth, 2011;Webb & Haycraft, 2019). Problematic parent-child interactions have been implicated in promoting childhood obesity risk (e.g., Anderson, Lemeshow, & Whitaker, 2014).…”
Section: Introductionmentioning
confidence: 99%